Tingkat Kemampuan Penggunaan Media Sosial Petani dalam Upaya Pemasaran Tanaman Hias di Desa Banjarejo Kabupaten Kediri (Jurnal Ilmiah Pertanian Nasional, 2024)
This research aims to find out what types of social media are widely used by ornamental plant farmers, find out the length of use of social media by ornamental plant farmers, know the function of ornamental plant farmers' social media for their business, determine the level of ability to use social media of ornamental plant farmers. The research sample consisted of 30 ornamental plant farmers who were chosen randomly. This research used qualitative descriptive methods and linear regression analysis to analyze the research data that has been collected. Based on the analysis and discussion results, it is known that Facebook social media is a type of social media that is widely used by ornamental plant farmers in Banjarejo Village, with 17 users out of 30 respondents. The duration of ownership of social media by ornamental plant farmers in Banjarejo Village is more than 3 years, with the usage of 30-40 hours per week. Ornamental plant farmers widely use social media in Banjarejo Village to market commodities. The ability of ornamental plant farmers in Banjarejo Village to use social media is on a sufficient scale. Penelitian ini memiliki tujuan untuk mengetahui jenis media sosial apa yang banyak digunakan oleh petani tanaman hias; mengetahui lama penggunaan media sosial oleh petani tanaman hias;  mengetahui fungsi media sosial petani tanaman hias untuk usahanya; mengetahui tingkat kemampuan penggunaan media sosial petani tanaman hias. Sampel penelitian berjumlah 30 orang petani tanaman hias yang dipilih secara acak. Penelitian ini menggunakan metode deskriptif kualitatif serta analisis regresi linear untuk menganalisis data penelitian yang telah dikumpulkan. Berdasarkan hasil analisis dan pembahasan diketahui bahwa media sosial facebook merupakan jenis media sosial yang banyak digunakan oleh petani tanaman hias di Desa Banjarejo, dengan jumlah pengguna 17 orang dari 30 responden. Lama kepemilikan media sosial petani tanaman hias di Desa Banjarejo lebih dari 3 tahun dengan, lama penggunaan sebesar 30-40 jam per minggu. Fungsi media sosial yang banyak digunakan oleh petani tanaman hias di Desa Banjarejo untuk memasarkan komoditas. Tingkat kemampuan petani tanaman hias di Desa Banjarejo dalam penggunaan media sosial berada pada skala cukup.